Didactics of Mathematics Profile of Engineering Students: A Case Study in a Multimedia Engineering Degree - Maria Luisa Pertegal-Felices (MDPI AG, 2020)
Multimedia engineers develop digital content in a wide range of fields that require them to acquire skills in the development of web solutions for those fields. In this study, we evaluated the level of didactic knowledge of mathematics that Multimedia Engineering degree students possess. The aim was to determine whether they are prepared to conceive, design and develop educational multimedia tools for teaching mathematics to primary school children. For this evaluation, the Didactic−Mathematical Knowledge and Elementary Algebraic Reasoning (DMK/EAR) test was carried out on a sample of 50 students in the second year of a Multimedia Engineering Degree. The results were compared with those of teacher training students who receive specific training in mathematics didactics. The study shows that, for most of the variables analysed, the Multimedia student scored better or comparatively equal to the teaching trainee. In conclusion, students of Multimedia Engineering have a solid foundation in the didactics of mathematics, although some deficiencies have been detected in the cognitive dimension and the content in structures, which indicate that they would need to complete their training in these areas.